Fenomenologi Husserl sebagai Dasar Mengembangkan Filsafat dan Dasar Menentukan Ukuran Kebenaran - Sri Soeprapto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
The aim of this research is to evaluate Husserl's phenomenology in order to be used as a foundation in developing philosophy. Husserl develops phenomenology as a philosophical method in order to find an evidence truth. Husserl's phenomenology is very important to develop philosophy as a scientific analysis.This research is the literature study on Husserl's phenomenology. The primary source are the books of Husserl. Some element of philosophical analysis that are interpretation, comparative, and hermenutic were used in analysing the data collected.The result of the research shows that phenomenology do not emphasize inductive apporch but used on intuitive insight. Phenomenology based on a phenomenon but on intensionality. The main function of intentionality is to reveral a covered of reality by the way objectivation, identification, and to systematize all of the nature or the essence of the object. The methodogical steps are phenomenological reduction, eidetic reduction, and transendental reduction. The enquiry steps are the enquiry of the particular phenomenon, the universal phenomenon, the nature of phenomenon, the existence, the insight of consciousness, to put off the existence of phenomenon, and to interpret the meaning of those phenomenon. The enquiry steps of phenomenology can be used to decide a criterion of the truth. The truth is not be based on the empirical verification and rationality only, but on comformity with intuitive insight as well.